DEVELOPING INCLUSIVE COMPETENCIES IN MATHEMATICS TEACHING METHODS (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article examines the development of inclusive teacher competencies in mathematics teaching in a modern education environment. It examines the essence of inclusive competencies, their structure, and their importance for ensuring students' equal access to educational resources. Particular attention is paid to the specifics of teaching mathematics in an inclusive environment, including the need to consider individual learning needs, differentiate content, and adapt teaching methods.
Keywords: INCLUSIVE education, teacher competencies, mathematics teaching, differentiated learning, universal learning design, educational environment.